2015
DOI: 10.1080/09658211.2015.1059860
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and self-defining memories in the context of health concerns

Abstract: Individuals with health anxiety report experiencing a strong sense of vulnerability to illness. Such beliefs may be driven by the biased recollection of past illness-related events. However, little research has explored the role of memory in health anxiety. In other disorders, rumination has also been identified as a process that leads individuals to recall memories dominated by the content of their concerns. This study examined the proposition that rumination might impact the content of "self-defining" autobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Blagov and Singer (2004) found a connection between the psychological well-being or social adjustment of individuals with the affect they show in their narratives. Continuing with particular aspects of SDMs, Moffitt and Singer (1994) found people whose SDMs are developed around their attainments showed more positive affect about these memories Regarding the association between SDMs and aspects of health, higher health anxiety levels have been associated with the retrieval of SDMs that were particularly negative (Sansom-Daly et al, 2016). The authors suggested that participants with high levels of health anxiety attributed greater value to negative beliefs about themselves and about illness/death, in line with previous results of Wells and Hackmann (1993).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Blagov and Singer (2004) found a connection between the psychological well-being or social adjustment of individuals with the affect they show in their narratives. Continuing with particular aspects of SDMs, Moffitt and Singer (1994) found people whose SDMs are developed around their attainments showed more positive affect about these memories Regarding the association between SDMs and aspects of health, higher health anxiety levels have been associated with the retrieval of SDMs that were particularly negative (Sansom-Daly et al, 2016). The authors suggested that participants with high levels of health anxiety attributed greater value to negative beliefs about themselves and about illness/death, in line with previous results of Wells and Hackmann (1993).…”
Section: Introductionsupporting
confidence: 70%
“…Mood has also been connected to the memory affectivity (Boyano & Mora, 2015). In previous studies, variables of the SDMs have been linked to well-being or health, (e. g.: Blagov & Singer, 2004;Lardi et al, 2010;Sansom-Daly et al, 2016). For example, higher psychological well-being has been related to narrative memories narrated more related to achievements, which are central to SDMs.…”
Section: Introductionmentioning
confidence: 98%
“…Traits likely influence SDM affect indirectly, by biasing mood and cognitive‐affective processes. Internalizing psychopathology (Sanson‐Daly et al., 2015) and attachment insecurity (Sutin & Gillath, 2009) may promote negative affect in SDMs and, perhaps, reduce their positive affect. Emotional avoidance may limit the use of positive memories to repair mood (Vanderlind et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2014) found that student's level of health anxiety symptoms was associated with the number of illness-related episodic future thoughts reported, but not with the number of illnessrelated autobiographical memories reported. Sansom-Daly et al (2016) examined self-defining memories and found that students with high scores of health anxiety did not identify more illnessrelated self-defining memories than students with low scores, but higher levels of health anxiety symptoms were associated with reporting more negative self-defining memories.…”
Section: Introductionmentioning
confidence: 99%